2005
DOI: 10.1385/ep:16:1:067
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietins Are Expressed in the Normal Rat Pituitary Gland

Abstract: Interaction of vascular endothelial growth factor (VEGF) with the angiopoietins (Ang) is an essential component of angiogenesis. Localization of VEGF in the anterior pituitary raises the possibility that Ang must be present in the pituitary gland as well. In this study Ang expression was detected in the normal rat pituitary gland at the gene level by reverse-transcriptase polymerase chain reaction and at the protein level by immunohistochemistry. The latter was analyzed by both light and confocal microscopy. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Ang-1 promotes endothelial cell survival (protection from apoptosis) through the Akt pathway and stimulates endothelial cell migration, sprouting and tube formation. The cells that produce Ang-1 and Ang-2 in the anterior pituitary are the gonadotrophs, which is in striking contrast with the neural lobe where strong expression is seen in endothelial cells ( 816 ). It is remarkable that, in addition to angiopoietins, gonadotrophs produce FGF-2 and VEGF, which may be relevant to the neovascularisation from meningeal vessels into the postero-lateral zone of the anterior pituitary, known to be rich in gonadotrophs and lactotrophs (see earlier in this section).…”
Section: Paracrine Control By Connective Tissue Cells Endothelial Cementioning
confidence: 99%
“…Ang-1 promotes endothelial cell survival (protection from apoptosis) through the Akt pathway and stimulates endothelial cell migration, sprouting and tube formation. The cells that produce Ang-1 and Ang-2 in the anterior pituitary are the gonadotrophs, which is in striking contrast with the neural lobe where strong expression is seen in endothelial cells ( 816 ). It is remarkable that, in addition to angiopoietins, gonadotrophs produce FGF-2 and VEGF, which may be relevant to the neovascularisation from meningeal vessels into the postero-lateral zone of the anterior pituitary, known to be rich in gonadotrophs and lactotrophs (see earlier in this section).…”
Section: Paracrine Control By Connective Tissue Cells Endothelial Cementioning
confidence: 99%
“…Nag et al [22] reported the localization of both Ang-1 and Ang-2 in scattered PAS positive adenohypophysial cells rather than in endothelial cells. There is also accumulating evidence that implicates Ang-2 in tumor progression [23].…”
Section: Angpt2 (Angiopoietin 2)mentioning
confidence: 99%
“…nag et al (18) reported that the localization of both anG-1 and anG-2 occurs in scattered periodic acid-Schiff (paS)-positive adenohypophysial cells rather than in endothelial cells. accumulated evidence also indicates that the production of anG-2 is implicated in tumor progression (19).…”
Section: Angpt2 (Angiopoietin 2)mentioning
confidence: 99%